The Oppositions “Top – Bottom” and “Movement up – Movement down” as Axiological Markers of the Concept “Life” - Бобро, Марія Павлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article analyses the peculiarities of the evaluative representation of the concept LIFE by the oppositions “top – bottom” and “movement up – movement down”. It points out the characteristic features of the nationally marked negative perception of the bottom as opposed to positive evaluation of the top. The images of static stay at the top or bottom that metaphorise social, psychological and moral-ethic dimensions of life are studied, among them such life states and phenomena as wealth–poverty, social status, freedom–subjugation, alcohol and drug addiction and such psychological characteristics as person’s mood, state of mind. The movement up or down is described as a symbol of changes in the above mentioned life states as well a symbol of the biological aspects of a person’s life, which accentuates the correlations “movement up – illness”, “movement down – recovery”. Life states as represented by the metaphorical top and bottom are considered in the light of mythological and Christian beliefs of Ukrainian people. The images “sky”, “heaven”, “ground”, “wings”, “head”, “legs” are singled out as top–bottom specifiers.